2020
DOI: 10.21203/rs.2.16384/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity and prevalence of various types of mental ill-health in a general adult population: Age and sex differences

Abstract: Background Taking a broad approach, the aim of this study was to better understand the extent of severity and prevalence in various types of mental ill-health across age groups and sexes in the general adult population. A first objective was to determine symptom severity of anxiety, depression, insomnia, burnout and somatization in combinations of different age groups and sex. A second objective was to determine prevalence of caseness of these types of mental ill-health in both absolute and relative terms in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…19 This sexdependent difference is also documented in current studies on the development and prevalence of mental disorders such as anxiety disorders, insomnia, and burnout. 20 Independent of the underlying genesis of the wound, women in our study also had significantly greater impairment in the psychological Wound-QoL subscale scores as well as in total Wound-QoL scores. Psychological factors as measured with the Wound-QoL include in particular worries and fears, for example, of bumping into the wound, of the development of further wounds and/or worsening of existing wounds, and frustration over the slow healing process.…”
Section: Wound-qol Related To Sexmentioning
confidence: 50%
See 1 more Smart Citation
“…19 This sexdependent difference is also documented in current studies on the development and prevalence of mental disorders such as anxiety disorders, insomnia, and burnout. 20 Independent of the underlying genesis of the wound, women in our study also had significantly greater impairment in the psychological Wound-QoL subscale scores as well as in total Wound-QoL scores. Psychological factors as measured with the Wound-QoL include in particular worries and fears, for example, of bumping into the wound, of the development of further wounds and/or worsening of existing wounds, and frustration over the slow healing process.…”
Section: Wound-qol Related To Sexmentioning
confidence: 50%
“…19 This sex‐dependent difference is also documented in current studies on the development and prevalence of mental disorders such as anxiety disorders, insomnia, and burnout. 20 …”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, the prevalence of stress among its adult population was reported to be 74% 20 . In Sweden, the prevalence of stress reported from a nationally representative study among adults were 14.0% 21 . The prevalence of stress in India, based on a national mental health survey was 3.7% 22 .…”
Section: Methodsmentioning
confidence: 98%
“…20 In Sweden, the prevalence of stress reported from a nationally representative study among adults were 14.0%. 21 The prevalence of stress in India, based on a national mental health survey was 3.7%. 22 In Myanmar, it was reported that 18% of adults aged 18-49 years old suffer from stress.…”
Section: The Associations Between Psychological Stress Sleep Deprivation and T2dmmentioning
confidence: 99%
“…Inconsistent with our indings, a study by Per Hoguland also suggested that anxiety, sleeplessness and burnout were specifically severe and prevalent in younger females. Men of middle age group have a higher occurrence of mental ill-health compared to other age groups of men, with the lowest severity and prevalence in the age span 60-69 years (Höglund et al, 2020).…”
Section: Pearson Correlationsmentioning
confidence: 96%